Eficiencia del modelo pedagógico de enseñanza de los estilos básicos de natación competitiva a niños con parálisis cerebral (Effect of training using the technology of teaching basic competitive swimming techniques to children with cerebral palsy) - Radziejowski, Paweł; Tomenko, Oleksandr; Bosko, Vasyl; Korol, Svitlana; Serhiienko, Volodymyr; Dotsyuk, Lidiia; Kushnir, Iryna; Galan, Yaroslav; Lohush, Lesia; Tsybanyuk, Oleksandra (Retos, 2022)
Resumen: Objetivo: Según muchos estudiosos destacados, el deporte es fundamental para la adaptación social y la integración de las personas con discapacidad. Por lo tanto, es importante investigar modelos innovadores para enseñar brazadas de natación competitiva a niños con parálisis cerebral. El objetivo del estudio es diseñar el modelo pedagógico de enseñanza de los estilos básicos de natación competitiva a niños con parálisis cerebral y evaluar su efectividad para dominar el estilo de natación estilo crol. Material y métodos: Se utilizó una metodología de investigación selectiva. Implicó la recopilación directa de datos gracias a la encuesta a los participantes. Los resultados mostraron que el nivel de dominio de la brazada de natación utilizado por los niños que aplicaron este modelo diseñado fue objetivamente mayor en comparación con los mismos indicadores de entrenamiento relacionados con el método tradicional. Conclusiones: Basándonos en la evaluación de la eficiencia de la brazada de natación, creemos que el modelo pedagógico propuesto de enseñar las brazadas básicas de natación competitiva a niños con parálisis cerebral es eficaz.Abstract. Purpose: According to many scholars, sport is essential for social adaptation and integration of people with disabilities. Therefore, it is important to research innovative technologies for teaching competitive swimming technique to 8-10-year- old children with cerebral palsy. The aim of this study is to develop the technology of teaching competitive swimming techniques to children with cerebral palsy and to evaluate its effectiveness for mastering the front crawl swimming technique. Materials and methods: analysis of scientific literature, questionnaires (e-correspondence), pedagogical experiment, expert survey, determination of the coefficient of technique efficiency, statistical methods. A total of 15 qualified swimming coaches participated in this study. The experiment involved 29 children who were diagnosed with cerebral palsy. Results: the main means of technology implementation is the web-based information system SwimCP (Swimming with Cerebral Palsy), which promotes effective swimming teaching for children with cerebral palsy at the initial stage of sports training by selecting and recommending an approximate complex of exercises that take into account the peculiarities of motor disturbance in accordance with the specific form of cerebral palsy and the stage of motor activity training. Conclusion: using expert assessment and the coefficient of swimming technique efficiency determination, it is confirmed that the proposed technology of teaching basic competitive swimming techniques to children with cerebral palsy is effective.